Explanatory Analysis of Ancillary Revenues: Case Study of Three European Airlines - Anna Tomova; Zdenka Strmiskova (Communications, 2014)
This paper quantifies an impact of ancillary revenues on changes of airlines total revenues using the data of three European low-cost airlines during the period from 2006 to 2011. The analysis reveals that ancillary revenues are important in generating total revenues in a low cost airlines group in terms of dynamics and subsequent influence on profit/loss result. The research findings confirmed that ancillary revenues influenced changes of total revenues significantly achieving in prevailing cases double-digit percentage share in the changes of total revenues expressed as a whole. So, quantified impact of ancillary revenues dynamics on dynamic of total revenues is undoubtly important for overall dynamics of airlines total revenues. Our analysis based on quantitative approach of explanatory analysis also clearly identified ancillary revenues as pro-operational profit driver through its positive and not marginal impact on dynamics in total airlines revenues. This disclosure is in line with general assumption of considerable role of ancillary revenues in low cost airlines economics.